One-Pot Synthesis of Ultra-Small Pt Nanoparticles-Loaded Nitrogen-Doped Mesoporous Carbon Nanotube for Efficient Catalytic Reaction - Qian Zhang; Minying Wu; Yuanyuan Fang; Chao Deng; Hsin-Hui Shen; Yi Tang; Yajun Wang (Nanomaterials, 2023)
In this study, Pt nanoparticles-loaded nitrogen-doped mesoporous carbon nanotube (Pt/NMCT) was successfully synthesized through a polydopamine-mediated “one-pot” co-deposition strategy. The Pt source was introduced during the co-deposition of polydopamine and silica on the surface of SiO2 nanowire (SiO2 NW), and Pt atoms were fixed in the skeleton by the chelation of polydopamine. Thus, in the subsequent calcination process in nitrogen atmosphere, the growth and agglomeration of Pt nanoparticles were effectively restricted, achieving the in situ loading of uniformly dispersed, ultra-small (~2 nm) Pt nanoparticles. The method is mild, convenient, and does not require additional surfactants, reducing agents, or stabilizers. At the same time, the use of the dual silica templates (SiO2 NW and the co-deposited silica nanoclusters) brought about a hierarchical pore structure with a high specific surface area (620 m2 g−1) and a large pore volume (1.46 cm3 g−1). The loading process of Pt was studied by analyzing the electron microscope and X-ray photoelectron spectroscopy of the intermediate products. The catalytic performance of Pt/NMCT was investigated in the reduction of 4-nitrophenol. The Pt/NMCT with a hierarchical pore structure had an apparent reaction rate constant of 0.184 min−1, significantly higher than that of the sample, without the removal of the silica templates to generate the hierarchical porosity (0.017 min−1). This work provides an outstanding contribution to the design of supported noble metal catalysts and also highlights the importance of the hierarchical pore structure for catalytic activity.